(untitled) (MMIT Proceedings, 2024)
In the article, issues such as global digitalization, rapidly changing economic processes, ensuring the country’s economic security require the formation of new professional competencies of customs specialists, the introduction of new approaches to the development of an innovative environment in customs education, as well as special psychological education programs that help self-realization in innovative and entrepreneurial activities and proposals have been developed regarding the appropriateness of development and implementation of technologies.